The Effect of Company Image and Word of Mouth on Consumer Decision-Making in Private Recruitment Agencies - Khotimah, Khotimah; Prasetyo, Heru Eko; Nurchayati, Nurchayati; Mardiyono, Aris (Research Horizon, 2024)
This study aims to analyze the effect of company image and Word of Mouth (WOM) on decisions to use Indonesian labor services at PT Alwidah Jaya Sentosa, Batang Regency, Central Java Province. The research population is Indonesian migrant worker who have worked abroad through the labor the company. This study uses multiple linear regression methods with a sample of 60 people. The results showed that partially, company image and WOM had a positive and significant effect on the decision to use the company. The significance value obtained (p < 0.05) indicates that the better the company's image and WOM generated from the positive experience of migrant workers who have left abroad, the more likely prospective workers choose to use the company's services. This shows the importance of the company's efforts in building a good image and utilizing WOM to strengthen the decision of prospective migrant workers to use the company's services. This study implies that companies should focus on improving their image through effective branding and communication strategies, as well as maximizing WOM as a marketing tool to increase the number of workers who use labor distribution services in the future.